NON-GOVERNMENTAL ORGANIZATIONS IN POLAND: THEIR ROLE AND SOURCES OF FINANCING - Magdalena Dąbkowska-Dworniak (Polityki Europejskie, Finanse i Marketing)
Non-governmental organizations (NGOs) are institutions that belong most often to the social service sector, whose goals are to meet the specific needs of people that are not being met, or not being met adequately, by commercial organizations or state administrations. Such NGOs work to help citizens develop and to improve themselves and their life situations. This article presents an overview of the role played by NGOs in Poland and how they are funded.